2015
DOI: 10.3390/ma8062994
|View full text |Cite
|
Sign up to set email alerts
|

The Composites of Graphene Oxide with Metal or Semimetal Nanoparticles and Their Effect on Pathogenic Microorganisms

Abstract: The present experiment describes a synthesis process of composites based on graphene oxide, which was tested as a carrier for composites of metal- or metalloid-based nanoparticles (Cu, Zn, Mn, Ag, AgP, Se) and subsequently examined as an antimicrobial agent for some bacterial strains (Staphylococcus aureus (S. aureus), methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli (E. coli). The composites were first applied at a concentration of 300 µM on all types of model organisms and their effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 53 publications
(65 reference statements)
0
23
0
Order By: Relevance
“…Moreover, GO has a 2D planar structure with a high specific area which can introduce interactions with the polymer matrix. Recent studies have demonstrated that GO is a biocompatible material, and has antibacterial ability with mild cytotoxicity [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The antibacterial activity of graphene and graphene derivatives is found to involve membrane puncture [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, GO has a 2D planar structure with a high specific area which can introduce interactions with the polymer matrix. Recent studies have demonstrated that GO is a biocompatible material, and has antibacterial ability with mild cytotoxicity [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. The antibacterial activity of graphene and graphene derivatives is found to involve membrane puncture [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…But the applications of graphene are limited because of the expensive nature of its mass production and the main problem is graphene has the tendency to stack due to vander-Waals interactions between its layers. This problem can be overcome by hybridising Graphene with metal oxide nanoparticles [10,11]. GO is used as a starting material for fabrication grapheme-based field effect transistor (FET).…”
Section: Application Of Go-metal Oxide Mixed Nanocompositesmentioning
confidence: 99%
“…These groups disturb the aromatic regions in the basal planes, that is why the layer of graphene oxide consist of both aromatic regions and oxidized aliphatic six-membered rings, which leads to distorted sp3-hybridized geometry and results in the insulating property of Graphene oxide. Normally Graphene oxide is a poor conductor but treatment with heat, light or chemical reduction most of graphene's properties can be restored [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…These differences were attributed to the bacterial cell wall, the surface protective effect of the outer membrane, and the ability to respond to the external environment . Membrane stress produced by the sharp edges of GO nanosheets also contributes to the antibacterial and antibiofouling performance of the complexes …”
Section: Antibacterial Activity Of Composite Materials Based On Graphmentioning
confidence: 99%